Description of the male of the rare Madagascan species Pseudorphnus hiboni with notes on the genus Pseudorphnus (Coleoptera: Scarabaeidae: Orphninae) - Frolov, Andrey V.; Montreuil, Olivier (Zootaxa, 2006)
A male of Pseudorphnus hiboni Paulian is described from material recently collected in Ranomafana National Park (eastern Madagascar). The species is compared with the two other known species of the genus. Notes on biology and distribution are given.